Nurse Communication Towards the Rights of Patients Involved in Health Service Participation at Ungaran Hospital - Nurhayati, Susi; Chotimah, Siti Chusnul (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2021)
Introduction: The provision of health services to patients involves nurses as caregivers to patients who are sick or healthy through communication. However, there is data providing information that is not optimal to patients, resulting in an increase in patient complaints. Objectives: The purpose of this study was to determine the communication of nurses towards the rights of patients involved in health services participation at Ungaran Hospital. Methods: The research method was quantitative with a cross-sectional approach to 97 samples measured using a questionnaire instrument and analyzed using chi-square. Results: The results of nurse communication relate to the patient's right to be involved in health service participation at Ungaran Hospital with a p-value of 0.000. The need for the ability of patients and families to know information related to their health and the patient's right to obtain information about nursing health actions so that they can participate in improving their health status.